Pengaruh Waktu Elektroplating Terhadap Laju Korosi Baja AISI 1020 Dalam Medium Korosif NaCl 3% - Aisiyah Putri Sandi; Ediman Ginting Suka; Yayat Iman Supriyatna (Jurnal Teori dan Aplikasi Fisika, 2017)
The influence of electroplating time Zn-Mn to corrosion rate of AISI 1020 steel in corrosive medium NaCl 3% had been researching. This research used time variation 10, 20, 30, 40, and 50 seconds. Corrosion rate testing is done by soaking the steel for 168 hours in corrosive medium NaCl and calculated with the loss of steel weight. The result showed that the longer electroplating time that used, caused the increasing of mass and Zn-Mn content of steel. It can make the corrosion rate will be decreased. The lowest corrosion rate obtained at 50 seconds electroplating time and 60 mA/cm2 current density is 0,059 mmpy. XRD characterization of steel without electroplating after corrosion rate testing showed the changing of phase from iron into oxide phase magnetite (Fe3O4). The analyze of metallurgical microscope showed the better layer with the increasing time, whereas after corrosion rate testing the steel surface were cracks.